Inside Back Cover: Activation of Ultrathin Films of Hematite for Photoelectrochemical Water Splitting via H2 Treatment (ChemSusChem 9/2015). Issue 9 (4th May 2015) - Moir, Jonathon; Soheilnia, Navid; Liao, Kristine; O'Brien, Paul; Tian, Yao; Burch, Kenneth S.; Ozin, Geoffrey A.
<x xml:space="preserve">Abstract</x> The Inside Back cover picture shows ultrathin films of α‐Fe2O3 before and after treatment in 5 % H2 in Ar at 450 °C. The hydrogen treatment creates oxygen vacancies in the iron oxide lattice, resulting in a non‐stoichiometric hematite phase that is active for photoelectrochemical water oxidation. Electrochemical impedance spectroscopy reveals the buildup of a surface state capacitance that is only present for the hydrogen treated films when under illumination, at the point of photocurrent onset. A concomitant decrease in charge trapping resistance suggests that this is due to a build‐up of photogenerated holes at the surface of the H2‐treated films, which allows the water oxidation reaction to proceed. More details can be found in the Full Paper by Moir et al. on page 1557 (DOI: 10.1002/cssc.201402945).